Properties of Venezuelan Equine Encephalomyelitis Virus Accompanying Attenuation In Vitro - Soper, William T. (1967)
Virus obtained during serial plaque passage of the virulent parent egg seed (PES) of the Trinidad strain of Venezuelan equine encephalomyelitis (VEE) virus produced only large plaques during either 3 serial plaque passages in chick fibroblasts or 10 plaque passages in L cells, and was lethal for mice by the intraperitoneal route. Virus showing these characteristics was designated the stable large-plaque (Ls) type. In contrast, virus obtained during serial plaque passage of the attenuated 9t strain in chick fibroblasts formed only very small plaques and was not lethal for mice by the intraperitoneal route. Virus showing these properties was designated the stable small-plaque (Ss) type. Under other passage conditions, however, large-plaque virus that yielded about 90% large and 10% small plaques was obtained; this virus was designated the unstable large or Lu type because it differed from the Ls type, which yielded only large plaques. The Lu type continued to yield the same ratio of large to small plaques for several plaque-to-plaque passages. In addition, small-plaque virus that yielded both large and small plaques and that showed a reduced capability to infect mice was also recovered. This virus was designated the unstable small or Su type because it differed from the Ss type in its higher level of virulence and in its plaque-forming properties. Thus, based upon the properties of virulence for mice and plaque size, four viral types could be discerned. The evidence suggests that serial passage in cell culture imposed environmental pressures that sequentially selected the following viral types: Ls, Lu, Su, and Ss.